A Theoretical Review on the Status and Trend of Exports (Goods and Services) and Investments (Foreign and Domestic) in Assam and North-East India and their Untapped Impact on the Economic Growth of the Region: The Story so far - Barua, Rashmita; G G, Banik (Journal of Management and Science, 2013)
A number of studies reveal that export expansion is widely regarded as a means to attain higher rate of economic growth. In a dynamic setting, trade usually enhances technological up-gradation, higher rates of productivity, attracts inward investment and facilitates economic growth. One of the most viable development strategies for a country‟s economic success is to find its own niche in the global marketplace, which means to be able to tap the demands of the world economy. Many developing countries have been trying to overcome a dismal economic situation by promoting international trade. In these efforts, exports have been viewed as an „engine‟ ofeconomic growth. With the emergence of the World Trade Organization, the institutional framework for freer multilateral movement of goods and services has been strengthened. Although the Indian Economy has been benefited from the time new economic reforms were initiated since 1991, North-Eastern Region still remains to be far from the purview of India‟s rapid development. With its geographical remoteness, inherent deficiency in infrastructure and the bad publicity for recurrent ethnic strife and militant activities, the region obviously could not become an attractive destination for private and foreign capital investment. But in this period of globalization, where closer cross-border economic ties are being speeding up in many parts of the world, border trade has come to be looked upon with a lot of expectation in this region to break free from the shackles of geographic remoteness. Given the natural and human resource potential of Assam, the need for higher growth has recently been felt by various sections of the people as well as the State and Central Governments.